Time-Dependent Density Functional Theory - Marques, Miguel A.L; Ullrich, Carsten A.; Nogueira, Fernando; Rubio, Angel; Burke, Kieron; Gross, Eberhard K. U. (Lecture Notes in Physics, 2006)
Time-dependent density functional theory (TDDFT) is based on a set of ideas and theorems quite distinct from those governing ground-state DFT, but emphasizing similar techniques. Today, the use of TDDFT is rapidly growing in many areas of physics, chemistry and materials sciences where direct solution of the Schrödinger equation is too demanding. This is the first comprehensive, textbook-style introduction to the relevant basics and techniques.